2014
DOI: 10.3109/01480545.2014.919583
|View full text |Cite
|
Sign up to set email alerts
|

In vitroimmunosuppressive and cytotoxic activities ofTripterygium wilfordiiextract

Abstract: Tripterygium wilfordii Hook. f. (TW) is a traditional herbal medicine which has been widely used for the treatment of rheumatoid arthritis and other autoimmune diseases. However, adverse reactions of TW such as hepatotoxicity and nephrotoxicity have been frequently reported in clinic. With the aim to evaluate the potency and toxicity of TW, we collected eleven batches of TW from different localities across Chinese mainland, and investigated the inhibition of their methanol extracts on the proliferation of mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…32,33 Tripterygium wilfordii is a widely used herbal medicine for the treatment of rheumatoid arthritis and other autoimmune diseases; however, its adverse reactions including hepatotoxicity and nephrotoxicity have been frequently reported in the clinic. 34 CM is a traditional Chinese herb medicine. Its nature of a crude drug suggests that it is a multi-effective component, which might target many molecules in the signaling of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Tripterygium wilfordii is a widely used herbal medicine for the treatment of rheumatoid arthritis and other autoimmune diseases; however, its adverse reactions including hepatotoxicity and nephrotoxicity have been frequently reported in the clinic. 34 CM is a traditional Chinese herb medicine. Its nature of a crude drug suggests that it is a multi-effective component, which might target many molecules in the signaling of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Tripterygium wilfordii Hook. F., known as Lei Gong Teng or ‘thunder duke vine’ in Chinese, is a commonly used medicinal plant with anti‐inflammatory, immunosuppressive and anticancer effects (Sylvester et al , He et al ). The history of its medicinal usage can be traced back to the Ming dynasty (AD 1476).…”
Section: Introductionmentioning
confidence: 99%
“…Tripterygium wilfordii (TW) is a type of traditional Chinese medicine that has been used to treat a variety of primary and secondary glomerular diseases due to its effectiveness in attenuating proteinuria ( 8 ). Previous studies have demonstrated that TW has potent anti-inflammatory and regulatory properties, as well as the ability to promote mesangial cell apoptosis and protect podocytes from inflammatory injury ( 9 , 10 ). TW has been extensively used in China for the treatment of autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus (SLE), nephrotic syndrome ( 11 ), and has been used to treat patients with DN ( 12 ); however, it has not yet been determined whether TW is able to modulate Wnt/β-catenin signaling in kidney tissue.…”
Section: Introductionmentioning
confidence: 99%